Understanding Gender-Based Sexual Violence Against Women and Girls: Breaking the Culture of Silence - Sciarrino, Nicole A.,; Davis, Brittany C., (Lexington Books, 2023)
Gender-based sexual violence is a widespread public health problem affecting people of all ages and from diverse backgrounds. Although both women and men experience sexual trauma across countries and contexts (e.g., military vs. civilian), prevalence rates of sexual trauma are higher among women, and women and girls may often be targeted due to their sex and rigidly held beliefs about gender roles. Experiences of sexual violence can have a myriad of negative outcomes for survivors, including implications for mental health and physical health difficulties. The content of this book encompasses a foundation for understanding the impact of gender-based sexual violence, common mental and physical health difficulties associated sexual assault, and trauma-informed care. This volume also addresses evidence-based psychotherapies for trauma survivors as well as emotional difficulties that may affect providers who work with this population (e.g., burnout, secondary traumatic stress). After reading this book, the authors hope readers have a deeper understanding of gender-based sexual violence and can meaningfully apply the practical skills provided throughout this text, whether in support of loved ones or in their daily work. Finally, the authors hope all readers experience decreased stigma, including self-stigma, related to gender-based violence.